Evaluasi Program Pelatihan Guru di Pusdiklat Tenaga Teknis Pendidikan dan Keagamaan Kementerian Agama Republik Indonesia - Hasyim Asyari; Tengku Rusman N; Astina Riyana (Tadbir : Jurnal Studi Manajemen Pendidikan, 2020)
This study aims to evaluate the Teacher Training Program at Training Center for Education and Religious Technical Personnell. The basic problem is that there is no post-training evaluation as an integral part of the evaluation of training implementation. The evaluation model used in this study is the Kirkpatrick evaluation model which is reaction level, learning level, behavior level and result level to get a more comprehensive picture of the Teacher Training Program. This study uses a qualitative approach with descriptive methods. Data was conduct using questionnaire, interview, and document studies. The results of this study indicate that on reaction level, based on the results of the achievement analysis are in the high category, learning level of the program which are also in the high category, behavior level are in the high category, however result level of the program are in the moderate category. The findings of the evaluation of this result prove the importance of the training center conducting post-training evaluations to determine the impact of the training on the performance of participants and educational institutions. This research can be used as input for the Training Center to be consistent in evaluating both during training and after training as stated in Kirkpatrick's theory.